2017
DOI: 10.1105/tpc.17.00464
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Two-Tiered Plant Immunity and Sexual Reproduction by ANXUR Receptor-Like Kinases

Abstract: Plants have evolved two tiers of immune receptors to detect infections: cell surface-resident pattern recognition receptors (PRRs) that sense microbial signatures and intracellular nucleotide binding domain leucine-rich repeat (NLR) proteins that recognize pathogen effectors. How PRRs and NLRs interconnect and activate the specific and overlapping plant immune responses remains elusive. A genetic screen for components controlling plant immunity identified ANXUR1 (ANX1), a malectin-like domain-containing recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 64 publications
0
93
0
1
Order By: Relevance
“…In addition, we observed that a lack of a functional FER, but not ANX1 or ANX2, resulted in altered plant defences against Pst DC3000 (Figs 2 and S2) when dip inoculated with high inoculum concentration [1 3 10 8 colony-forming units (CFU)/mL]. However, in a different experimental set-up (syringe infiltration with 5 3 10 4 CFU/mL), Mang et al (2017) observed that anx1-2 and anx2-2 leaves can support smaller bacterial populations than Col-0 leaves. Moreover, ANX1 may act as a negative regulator of immunity by interfering with FLS2-BAK1 formation under flagellin elicitation (Mang et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In addition, we observed that a lack of a functional FER, but not ANX1 or ANX2, resulted in altered plant defences against Pst DC3000 (Figs 2 and S2) when dip inoculated with high inoculum concentration [1 3 10 8 colony-forming units (CFU)/mL]. However, in a different experimental set-up (syringe infiltration with 5 3 10 4 CFU/mL), Mang et al (2017) observed that anx1-2 and anx2-2 leaves can support smaller bacterial populations than Col-0 leaves. Moreover, ANX1 may act as a negative regulator of immunity by interfering with FLS2-BAK1 formation under flagellin elicitation (Mang et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…However, in a different experimental set‐up (syringe infiltration with 5 × 10 4 CFU/mL), Mang et al . () observed that anx1–2 and anx2‐ 2 leaves can support smaller bacterial populations than Col‐0 leaves. Moreover, ANX1 may act as a negative regulator of immunity by interfering with FLS2–BAK1 formation under flagellin elicitation (Mang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, two malectin-like RKs ANXUR1 (ANX1) and ANX2, which are receptors of RALF4 and RALF19, negatively regulate immune responses triggered by multiple patterns [18,19]. They constitutively associate with both FLS2 and BAK1, but interfere with flg22-induced FLS2-BAK1 complex formation to prevent excessive immune activation [19]. In the future, it will be interesting to test whether these negative regulatory components compete with positive regulatory components in the formation of PRR complexes.…”
Section: Composition Of Pattern-recognition Receptor Complexesmentioning
confidence: 99%